Entre cozinhas e assembleias: protagonismo feminino em duas ocupações urbanas de São Carlos-SP - Camargo, Maria Eugenia (Universidade Federal de São Carlos, 2025)
This monograph follows the life paths of Jéssica and Érica, leaders of two urban occupations located on the outskirts of São Carlos, in the interior of São Paulo. Using an ethnographic approach — which included participant observation, collaboration in daily activities, and semi-structured interviews — it examines the trajectories of these two women as they built their positions of leadership. The occupations’ community kitchens were taken as a privileged site of observation, given the symbolic and practical significance of food in a territory marked by food insecurity. The study is based on the hypothesis that care work — especially the preparation and distribution of food — is one of the main foundations of the authority exercised by these women. Observing their practices reveals how care plays a central role in the collective management of the territory and the political organization of the communities. This research thus highlights women’s leadership in urban occupations and the ways in which women reinvent political practice from the margins.
Between kitchens and assemblies: women's leadership in two urban occupations in São Carlos, SP
Keywords: Lideranças femininas; Ocupações urbanas; Cozinhas comunitárias; CIENCIAS HUMANAS::SOCIOLOGIA